Deep phlebography in postphlebitic syndrome - Palma, Eduardo C; Berriel, Hipólito (Cirugía del Uruguay, 1972)
The paper stresses the importance of deep phlebography in the study of postphlebitic syndromes and discusses the physiopathology of this disease.